Social Capital, Product Imitation and Growth with Learning Externalities - Agénor, Pierre-Richard; Dinh, Hinh T. (World Bank, Washington, DC, 2013)
Links between social capital, human capital, and product imitation are studied in an overlapping generations model of endogenous growth where the key benefit of social capital is to promote imitation. There is also a two-way interaction between imitation and human capital. Building social capital (which brings direct utility) requires time. Because life expectancy is endogenously related to human capital, time allocation between market work and social capital accumulation is also endogenously determined. Social capital accumulation depends also on access to infrastructure. The model is calibrated numerically for a low-income country. A policy that helps to promote social capital accumulation may be very effective to foster economic growth, even if it involves offsetting cuts in other productive components of government spending, such as education outlays or infrastructure investment. Offsetting cuts in infrastructure investment, however, may be less effective.